(untitled) (Experimental biology, 2016)
Options considered structural and functional organization of species genomes in terms of evaluation of promising species for breeding. System developed by the author genomic characteristics of evolutionary -labilnyh and evolutionarily conserved species is the basis for the selection of the raw material for breeding. Pee getting a raw material for an integrated approach (artificial selection, hybridization, ploidy regulation, inbreeding, inbreeding, mutagenesis) of classical genetics and breeding. At the same time take into account the origin and evolutionary development of the species. Specific types of plants or animals used as the starting material necessary level neproyavili morphogenetic plasticity, apparently dependent on the genetic constitution of the species. Accordingly, this gene is a genetic unit entire system type and polymorphic gene pool reflects the part of the genome.